Performance of an Item Response Theory-Based Computer Adaptive Test in Identifying Functional Decline - Cheville, Andrea L. (2012)
OBJECTIVE: To achieve a low respondent burden and increase the responsiveness of functional measurement by using an item response theory-based computer adaptive test (CAT), the Activity Measure for Post-Acute Care (AM-PAC) CAT. DESIGN: Two-year prospective cohort study. SETTING: Telephonic assessments from a quaternary medical center. PARTICIPANTS: Patients (N = 311) with late-stage lung cancer (LC). INTERVENTIONS: Monthly assessments for up to 2 years. Disease progression was determined via record abstraction. Anchor-based responsiveness techniques were used to compare AM-PAC-CAT score changes between global rating of change (GRC) question response levels, as well as between intervals when adverse clinical events or symptom worsening did and did not occur. Distribution-based responsiveness assessments included calculation of the standardized effect size (SES) and standardized response mean (SRM). MAIN OUTCOME MEASURES: AM-PAC-CAT, symptom numerical rating scales, and a GRC. RESULTS: Administration time averaged 112 seconds over 2543 interviews. AM-PAC-CAT score changes became more positive as GRC responses reflected more improved states: a lot worse (−11.62), a little worse (−1.92), the same (−.10), a little better (1.01), and a lot better (2.82). Score changes were negative when associated with adverse clinical events. The SES and SRM for score differences between 1 to 2 and 9 to 10 months prior to death were −.87 and −1.13, respectively. The minimally important difference estimate was defined by the mean CAT session SE at 2.0. CONCLUSIONS: The AM-PAC-CAT imposes a low, <2-minute, respondent burden, and distribution- and anchor-based methods suggest that is moderately responsive in patients with late-stage LC.